PENGARUH GAYA DOSEN MEMIMPIN SEBUAH PEMBELAJARAN TERHADAP PRESTASI DAN MOTIVASI BELAJAR UNIVERSITAS SINGAPERBANGSA KARAWANG - Nurjannah, Fitri; Syamsir, Syamsir; Ramadhan, Fadilah (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2022)
This research departs from the phenomenal factors of the low motivation to study economics students. This study aims to determine whether leadership has an effect on student motivation at Singaperbangsa Karawang University. The data taken in this study are the results of a survey conducted on students of the economics faculty of Singaperbangsa Karawang University. The method used in this research is quantitative with 2 independent variables and 1 dependent variable. The results showed that the regression equation model was significant based on the research data. There is a linear influence of leadership on student achievement and motivation to learn